Evaluation of Insulin Resistance and Glutathione-S-transferase in Iraqi Patients with Type 2 Diabetes Mellitus and Diabetic Peripheral Neuropathy - Hadeel Khalid Jaid; Fayhaa Muqdad Khaleel; Isam Noori Salman; Baydaa Ahmed Abd (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2022)
Diabetes mellitus type 2 (T2DM) is a metabolic disorder that influences above 450 million individuals around the world. Type 2 diabetes is a lack of insulin due to pancreatic β-cell malfunction and insulin resistance. This study aimed to detect insulin resistance using homeostasis model assessment (HOMA IR) and determined the correlation with glutathione-s-transferase (GST) activity in T2DM and neuropathy patients as a predictor of oxidative stress, which occurs when the oxidation-antioxidant equilibrium is disrupted. Reactive oxygen species causes vascular injury and a series of inflammation. In the present study, the results show there is no significant difference in diabetic patients (DM) and neuropathy patients (NU) versus healthy people in insulin resistance (p> 0.05). GST activity significantly differs between the patients and healthy groups (p≤0.05). Moreover, this study has reported an improvement in insulin resistance and high activity of GST in the patient's group as a warning sign of excessive oxidative stress. There was no evidence revealing a link between insulin resistance and GST. The present study has demonstrated that HOMA-IR had a positive relationship with fasting blood sugar and insulin in the neuropathy group and diabetic group and a negative relationship with high-density lipoprotein (HDL).